PATH-22. CLINICAL FEATURES AND MOLECULAR CHARACTERIZATION OF LEPTOMENINGEAL DISEASE IN PATIENTS WITH HIGH GRADE GLIOMA. (14th November 2022) - Shoaf, Madison; Chow, Frances; Xiu, Joanne; Glantz, Michael; Aulakh, Sonikpreet; Ashley, David; Lipp, Eric S; Lopez, Giselle; Sumrall, Ashley; Walker, Phillip; Spetzler, David; Nicolaides, Theodore; et al.
Abstract: INTRODUCTION: Leptomeningeal disease (LMD) is a challenging complication of high grade glioma (HGG) and critical questions remain unanswered regarding clinicopathologic risk factors, molecular associations, and optimal treatment. METHODS: Patients with molecularly-profiled HGG (Caris Life Sciences; Phoenix, AZ) with LMD at two institutions were included. Medical records were reviewed for clinicopathological characteristics, treatment, and outcome. Kaplan-Meier estimates of patient survival were performed on censored data using Cox's proportional hazard model. RESULTS: 43 patients (male: 33, female: 10; median age: 56 years) were identified, comprising 41 grade 4 (glioblastoma: 38; gliosarcoma: 2; H3K27M diffuse midline glioma: 1) and 2 grade 3 tumors (astrocytoma: 1; pleomorphic xanthoastrocytoma: 1). LMD diagnosed at HGG diagnosis (n=18) versus recurrence (n=22) was associated with longer post-LMD survival [pLMD-OS: 15.3m vs. 4.8m, HR: 0.07, 95% CI: 0.02-0.29, p=0.0004] but similar overall survival [mOS: 15.3m vs. 12.3m; HR: 0.82; 95% CI: 0.36-1.85; p=0.63]. Pathology-diagnosed LMD (n=15) versus MRI-diagnosed LMD (n=26) was associated with longer post-LMD survival [pLMD-OS: 15.4m vs. 5.2m, HR: 14.9, 95% CI: 0.01-0.30, p=0.0004] but similar overall survival [mOS: 17.1m vs. 12.3m; HR: 0.66; 95% CI: 0.3-1.58; p=0.38]. Post-LMD survival was significantly prolonged for supratentorial (n=28) versus infratentorial/spinal (n=4) locations regardless of the diagnostic modality [pLMD-OS: 2.6m vs. 11.3m, HR: 14.4, 95% CI: 2.73-75.7, p=0.0017], and did not significantly differ between symptomatic (n=20) and asymptomatic (n=23) patients [pLMD-OS: 4.8m vs. 11.2m, HR: 1.75, 95% CI: 0.82-3.77, p=0.15). pTERT mutation (81%), EGFR amplification (43%), and MGMT methylation (33%) were prevalent but IDH1 mutation was rare (2.8%). Comparison with a separate glioblastoma cohort (n=1400) suggested more frequent amplification of CHIC2, MDM4, and KDR, higher mutation rates of RUNX1, APC, and RAD51C, colder tumor microenvironment (TME), and lower expression of immune checkpoint-related genes. CONCLUSIONS: Clinicopathological characteristics affect post-LMD survival, and cohort comparison suggests molecular and TME differences in LMD-HGG tumors.